Self-Healing Concrete Using Bacteria Calcification from Karst Cave Environment - Ananto Nugroho; Agung Sumarno; Luna Nurdianti Ngeljaratan; Deni Zulfiana; Ni Putu Ratna Ayu Krishanti; Triastutil Triastutil; Eko Widodo (Jurnal Kimia Terapan Indonesia, 2019)
Karst regions in Indonesia have the uniqueness of the landscape and biodiversity. The karst is formed by the dissolution of rocks and the precipitation of mineral. In the cave, there are ornaments of stalactite and stalagmite which are formed by the process of mineral precipitation. We have isolated, screened, and identified the soil bacterium from the cave environment (Lysinibacillus macroides). These bacteria are able to precipitate calcium carbonate and can be developed as a self-healing agent concrete. We investigated the proportions and the properties of mixtures concrete containing lightweight aggregate and volcanic ash impregnated with bacteria. A comparison study was made by concrete cylinders subjected to compressive strength tests with and without the bacteria. It found that the strength of concrete with bacteria decreased by less than 10.56% for 28 days of cured specimens. This study showed that the effects of bacteria on the strength of concrete are not considerable. However, these bacteria are effective to repair in the microcrack less than 0.3 mm